1997
DOI: 10.1046/j.1365-2818.1997.2260781.x
|View full text |Cite
|
Sign up to set email alerts
|

A porous carbon film for the collection of atmospheric aerosol for transmission electron microscopy

Abstract: This paper describes a method of direct sampling of fine urban aerosol using porous carbon films, to increase collection efficiency and retain the structural integrity of the aerosol. A nuclepore membrane filter was coated with carbon and washed with chloroform to leave a clean porous carbon film on a 200‐mesh transmission electron microscope copper grid. The grid was attached to a clean nuclepore filter using carbon cement. Sampling was conducted for 1 h at 1.9 L min−1 flow rate. The porous carbon grid with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Dye et al reported that using porous carbon films to collect samples of fine urban aerosol could increase collection efficiency and retain the structural integrity of the aerosol. 6…”
Section: Separation Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dye et al reported that using porous carbon films to collect samples of fine urban aerosol could increase collection efficiency and retain the structural integrity of the aerosol. 6…”
Section: Separation Membranesmentioning
confidence: 99%
“…Nanoporous carbon films or membranes (NPCFs) of high quality and thinner than several tens of micrometres are attractive materials due to their many excellent properties such as thermal and chemical stability, high thermal conductivity and good electrical conductivity. [1][2][3] Because of their structural features (high specific surface area) and easily tunable nanoporosities, NPCFs are promising for various applications, for example, separation and purification, 4 adsorption, 5,6 catalysis, 7 and electrochemical capacitors. [8][9][10] NPCFs can be synthesized by hard-and soft-templating, pyrolysis of organic polymer precursors, chemical and physical vapor deposition and electrochemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Although numerous methods such as chemical vapor deposition, hydrothermal decomposition of carbide compounds, and polymer coating and pyrolysis have been developed for the fabrication of carbon film, [8][9][10] easily scalable self-supported nanoporous carbon films have not yet been obtained with any of them. The following promising methods for fabricating the pore structure of carbon film have recently been reported: colloidal silica imprinting, microbead patterning, and presynthesized mesoporous silica scaffolding.…”
mentioning
confidence: 99%